2016
DOI: 10.3390/su8080732
|View full text |Cite
|
Sign up to set email alerts
|

Investigations on the Energy Efficiency of Stratified Air Distribution Systems with Different Diffuser Layouts

Abstract: This paper investigated the influence of diffuser layouts on the energy performance of stratified air distribution systems (STRAD). The energy saving potentials of STRAD systems are theoretically analyzed. The cooling coil load of a STRAD system is proportion to the return air temperature, while inversely proportional to the exhaust air temperature. Based on that, numerical studies are conducted for the applications of STRAD systems in three typical building space types. Two evaluation indices are developed to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 13 publications
2
5
0
Order By: Relevance
“…When the height of the return air inlet was 0.3 m, the energy consumption was the lowest. Cheng et al [ 49 ] also had a similar conclusion. Due to the limitation of the experimental chamber conditions, the minimum return air inlet height was 0.7 m. In CFD, the heights of return air vents were calculated at 0.3 m, 0.7 m, 1.2 m, 1.6 m and 2.0 m, to make up for the lack of experiments.…”
Section: Resultssupporting
confidence: 54%
See 1 more Smart Citation
“…When the height of the return air inlet was 0.3 m, the energy consumption was the lowest. Cheng et al [ 49 ] also had a similar conclusion. Due to the limitation of the experimental chamber conditions, the minimum return air inlet height was 0.7 m. In CFD, the heights of return air vents were calculated at 0.3 m, 0.7 m, 1.2 m, 1.6 m and 2.0 m, to make up for the lack of experiments.…”
Section: Resultssupporting
confidence: 54%
“…Cheng et al [ 49 ] suggested that the return air vents in a small space could be located in a lower area to save the energy of the cooling coil. Heidarinejad et al [ 20 ] studied the effects of the heights of the side wall return air inlet and other parameters on the energy consumption, thermal comfort conditions and indoor air quality in UFAS, and found that reducing the height of return air inlet was more energy efficient.…”
Section: Resultsmentioning
confidence: 99%
“…For a system with the exhaust/return-split layout ( Fig. 5 ), Q coil is calculated by the following equation [ 75 , 76 ]: where Q spcae is the space cooling load (consisting of heat sources and external heat flux through walls), T e is the exhaust temperature, and T f is the fresh air temperature. The fresh air flow rate equals the exhaust flow rate for airtight spaces.…”
Section: Models and Methodsmentioning
confidence: 99%
“…The exhaust/return-split layout (Figure 1b) can reduce the cooling load further when thermal stratification exists. As explored by Cheng et al [8,9], this strategy involves trapping heat in the upper room area, thereby increasing the temperature of the exhaust air and relieving the cooling load. However, this approach introduces a trade-off: while it reduces energy consumption, it exacerbates vertical temperature gradients, potentially impacting thermal comfort.…”
Section: Introductionmentioning
confidence: 99%